DUALISME KEWENANGAN PENGAWASAN KOPERASI SIMPAN PINJAM (KSP) ANTARA KEMENTERIAN KOPERASI DAN UKM SERTA OTORITAS JASA KEUANGAN (OJK) - Perdana, M. Taufan; susetiyo, weppy; kasiani, kasiani (Fakultas Hukum, Universitas Islam Balitar, 2025)
This study juridically analyzes the dualism of supervisory authority over Savings and Loan Cooperatives (KSP) between the Ministry of Cooperatives and SMEs and the Financial Services Authority (OJK). Using a normative legal method, the research identifies regulatory ambiguity and overlap concerning licensing, guidance, and sanctions. The findings indicate that inconsistencies in legislation create supervisory gaps, which can harm KSP members. Therefore, this study recommends a revision and harmonization of regulations to clarify the authority of both institutions. New policies should be based on the characteristics of cooperatives as member-based, family-oriented entities to ensure optimal protection for their members. Keywords: Dualism of Authority, Cooperative Supervision, OJK